The big bang and the City of London - Catherine R. Schenk (IBF - Institut für Bank- und Finanzgeschichte, 2018)
Brexit poses an existential challenge the City of London as a European and global financial centre. The withdrawal of 'passporting' threatens the ability of financial institutions in London to sell services to customers in the EU, and this has prompted many predictions of London's financial demise. Banks are considering relocating staff and activities to other European centres such as Frankfurt, Dublin or Paris. Reflecting on London's history offers some insights into how The City might respond to this new challenge.
Keywords: G15; G18; N24; N44; 330